2013
DOI: 10.5535/arm.2013.37.2.247
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Removable Denture on Swallowing

Abstract: ObjectiveTo investigate the relationship between removable dentures and swallowing and describe risks.MethodsTwenty-four patients with removable dentures who were referred for videofluoroscopic swallowing study (VFSS) were enrolled. We evaluated the change of swallowing function using VFSS before and after the removal of the removable denture. The masticatory performance by Kazunori's method, sensation of oral cavity by Christian's method, underlying disease, and National Institutes of Health Stroke Scale for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
0
5
2
1
Order By: Relevance
“…The finding does not support a previous result in which wearing a removable denture appeared to create swallowing difficulties by increasing the duration of the swallowing process. 41 Unfortunately, the latter study did not distinguish subgroups based on the type of dentures (complete or partial), unlike the present study, which might explain the controversial result.…”
Section: Characteristiccontrasting
confidence: 69%
“…The finding does not support a previous result in which wearing a removable denture appeared to create swallowing difficulties by increasing the duration of the swallowing process. 41 Unfortunately, the latter study did not distinguish subgroups based on the type of dentures (complete or partial), unlike the present study, which might explain the controversial result.…”
Section: Characteristiccontrasting
confidence: 69%
“…While some studies [ 34 – 36 ••, 38 40 ] have suggested that denture wearing had positive effects on swallowing function, conversely, one study [ 41 ] indicated that denture wearing may have negative effects on swallowing function, especially the oral transit time (OTT) and oropharyngeal swallow efficiency (OPSE). OTT is the time from the moment at which the major bolus in the oral cavity begins to move rearwards to the moment at which the front end of the bolus arrives at the point of crossing between the lower edge of mandibular ramus and the tongue base.…”
Section: Effect Of Tooth Loss and Denture Wearing On Swallowing Problmentioning
confidence: 99%
“…OPSE is the value obtained by dividing the fraction of bolus swallowed through the esophagus by the total time taken to pass the oropharynx, and aspiration is the passing of food through the vocal fold [ 42 ]. Son et al [ 41 ] showed that OTTs were shortened and OPSE increased when dentures were removed compared to when dentures were worn. They discussed that the delay in OTTs and the decreases in OPSE observed after dentures were worn might be considered attributable to changes in masticatory performance or sensation within the oral cavity due to denture wearing.…”
Section: Effect Of Tooth Loss and Denture Wearing On Swallowing Problmentioning
confidence: 99%
“…All patients were evaluated by a physiatrist with an intrarater reliability of oropharyngeal swallowing efficiency of 0.87, based on MBSS. [ 21 ] The demographic and clinical characteristics of all patients were collected, including underlying diseases, performance of tracheostomy, feeding methods, radiologic findings before and after the swallowing study, total hospital stay, and days to discharge. Results suggesting pneumonitis, pulmonary edema, allergic responses, or chemotoxicity-related laboratory/vital findings were collected over 1 week after the evaluations.…”
Section: Methodsmentioning
confidence: 99%